Conditions of total coliform in the Aur River, Palembang City, South Sumatra, Indonesia - Matolisi, Elizabet; Damiri , Nurhayati; Imanudin, Momon Sodik; Hasyim, Hamzah (Journal of Degraded and Mining Lands Management, 2024)
Pathogenic microorganisms present in river water pollution are a serious health risk. Escherichia coli is a pathogen commonly found in water. Escherichia coli is an indicator of water contaminated with feces. These pathogens have an impact on human health. Aur River is one of the tidal rivers in Palembang City. From the observations, many people dispose of domestic waste into river bodies, so the river is at risk of being polluted by pathogenic microorganisms. When it recedes, the water looks pitch black, and when it is high, many people bathe, brush their teeth, and wash their clothes in this river. Thus, this study aimed to monitor water quality, including total coliform, of the Aur River Palembang City. The results of this monitoring can be used as the basis for making a policy and strategy to control the quality of this river water. This study was carried out on the Aur River, which is 2.5 km long. Measurements were made at three stations, namely at the upstream, middle, and downstream. Based on measurements of the pH, BOD, COD, DO, and total coliform concentrations, it is concluded that the Aur River has been polluted because the BOD, COD, DO, and total coliform were above the quality standards. The pH is still at the quality standard.